Determination of oil palm pollen fertility using staining techniques - Forster., B. P. (Malaysian Palm Oil Board, 2019)
The accurate determination of pollen fertility in oil palm (Elaeis guineensis Jacq.) is of critical importance in pollen storage as well as in germplasm exchange, especially for use in breeding. Pollen can be categorized as non-viable (dead), viable (alive, but not necessarily fertile) and fertile (potent) pollen. It is important, in practical terms, to be able to differentiate between these three categories and to determine their frequencies in a pollen sample. The effectiveness of different staining methods, using fluorescein diacetate (FDA), aceto-orcein, 4 '6-diamidino-2-phenylindole (DAP1) and pollen germination to predict pollen fertility were investigated. Although all of these methods gave similar results, FDA staining was found to be the best method in terms of time and resource efficiency.